The Impact of Fairy Tales on The Development of Children’s Moral Dimension Case study :Oscar Wild’s fairy tale The Happy Prince - Mokhtari ,Nacira; Hachani, Siham (Faculty of Letters and Foreign Languages Department of English, 2018)
The importance of stories in educating the moral imagination of the child provides the context for this thesis, which explores children’s responses to the moral dimension of fairy tales. Studies in child’s moral life, literary theory and children’s responses to reading also provide the empirical and theoretical background for this qualitative enquiry that compares a number of developing readers’ responses to fairy tales in a school and classroom context. Focusing on the features that distinguish their moral development, cultural improvements and educational effects. It identifies arrange of strategies children adopt to evaluate the moral world of fairy tales such as the use of moral touchstones, alternative narratives and to explore new vocabularies and to stimulate their critical thinking